2013
DOI: 10.1002/ceat.201200582
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heat Transfer on Micro‐Structured Surfaces Based on Entropy Production

Abstract: Surface structures with a well-defined shape and dimension in a staggered arrangement were evaluated in terms of their capability to improve the singlephase convective heat transfer in channels with small dimensions. Two evaluation criteria were used: (i) the thermal efficiency index, defined by the ratio of heat transfer enhancement and pressure drop increase, and (ii) the irreversible entropy generation which is determined by the entropy production rates through heat conduction and dissipation. Beside experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…To further increase the heat and mass transfer, we have designed and fabricated a microreactor with micro‐pin‐fin arrays (MPFAR), and our previous research results have shown several advantages of this microreactor for hydrogen production 12, 13. Jasch and Scholl have also shown that MPFAR with well‐defined shape, dimensions, and arrangement can improve convective heat transfer 14. However, as a fuel processor for application in fuel cell vehicles, a microreactor with a low hydrogen production rate due to a small reaction volume is not feasible and needs to be scaled up.…”
Section: Introductionmentioning
confidence: 99%
“…To further increase the heat and mass transfer, we have designed and fabricated a microreactor with micro‐pin‐fin arrays (MPFAR), and our previous research results have shown several advantages of this microreactor for hydrogen production 12, 13. Jasch and Scholl have also shown that MPFAR with well‐defined shape, dimensions, and arrangement can improve convective heat transfer 14. However, as a fuel processor for application in fuel cell vehicles, a microreactor with a low hydrogen production rate due to a small reaction volume is not feasible and needs to be scaled up.…”
Section: Introductionmentioning
confidence: 99%